Incidence of endemic ataxic polyneuropathy and its relation to exposure to cyanide in a Nigerian community - Oluwole, O (BMJ Group, 2003)
Background The occurrence of ataxic polyneuropathy in an endemic area in south west Nigeria has been attributed to exposure to cyanide from cassava foods. However, it has been shown that the prevalence of ataxic polyneuropathy is not high in several communities in the tropics where exposure to cyanide from cassava foods is high. Objectives To determine the incidence of ataxic polyneuropathy in an endemic community, and to compare the intake of cassava foods, exposure to cyanide, and levels of thiols in cases and controls. Methods A cohort of 3167 healthy subjects aged 10 years and over in Ososa, Nigeria, was followed for two years, screened, and examined neurologically. Ataxic polyneuropathy was diagnosed if sensory polyneuropathy and sensory gait ataxia were both present. Controls were selected randomly within 10 year age groups of subjects who screened negative. Intake of cassava foods, exposure to cyanide, concentrations of thiols (glutathione, cysteine, and γ glutamylcysteine) in plasma, and visual evoked potentials were measured. Results Person–years of follow up were 6246 for 1469 male and 1698 female subjects in the cohort. The incidence of ataxic polyneuropathy was 64 per 10 000 person–years (31 for male and 93 for female subjects). Multivariate odd ratios were 0.78 (95% CI 0.23 to 2.61) for intake of the commonest cassava food, and 1.64 (0.56 to 5.09) for concentration of thiocyanate in plasma. The concentration of thiols was less than the reference limits in two controls, but in none of the cases. The latency of P100 was prolonged in 20 cases (69%) compared with 14 controls (42%) (p<0.05). Conclusions The incidence of ataxic polyneuropathy is high in Ososa, Nigeria, but the intake of cassava foods, exposure to cyanide, and levels of thiols, are not related to the occurrence. These findings do not suggest that cyanide is the cause of endemic ataxic polyneuropathy.